Do Inventors Talk to Strangers? On Proximity and Collaborative Knowledge Creation - Riccardo Crescenzi; Max Nathan; Andrés Rodríguez-Pose (Institute for the Study of Labor (IZA), 2013)
This paper investigates how physical, organisational, institutional, cognitive, social, and ethnic proximities between inventors shape their collaboration decisions. Using a new panel of UK inventors and a novel identification strategy, this paper systematically explores the net effects of all these 'proximities' on co-patenting. The regression analysis allows us to identify the full effects of each proximity, both on choice of collaborator and on the underlying decision to collaborate. The results show that physical proximity is an important influence on collaboration, but is mediated by organisational and ethnic factors. Over time, physical proximity increases in salience. For multiple inventors, geographic proximity is, however, much less important than organisational, social, and ethnic links. For inventors as a whole, proximities are fundamentally complementary, while for multiple inventors they are substitutes.
Keywords: O31; O33; R11; R23; 330; innovation; patents; proximities; cities; regions; knowledge spillovers; collaboration; ethnicity